Optimal ordering and pricing decision for items following price sensitive quadratic demand under combined payment scheme - Shaikh, Azharuddin; Mishra, Poonam; Talati, Isha (Yugoslav Journal of Operations Research, 2023)
Three types of payments confront in business dealings viz. advance, cash and credit. A cash payment is ubiquitously practiced, while a credit payment scheme escalates sales and advance payment technique is implemented to avoid cancellation of orders. These are recognized as advance-cash-credit (ACC) payment scheme which is conventional in business transactions. By implicating ACC the aim is to determine optimal pricing and ordering policies. Inventory items observes quadratic demand being sensitive to unit selling price. Promising concavity of the profit function for both selling price and cycle time is posed numerically. Managerial insights are revealed as a concluding note.